Identification of rupatadine fumarate polymorphic crystalline forms in pharmaceutical raw materials - Castillo Henríquez, Luis (2018)
Polymorphism analysis of pharmaceutical raw materials is considered one of the most relevant evaluations that should be done. As we know, different crystal forms from the same molecule have differences in terms of their physicochemical properties. According to the crystal form used, researchers can obtain benefits for the development of a new product or it can also imply a disadvantage for the formulation of the product. The present study focuses on the identification of crystalline forms in Rupatadine Fumarate raw material samples. The active pharmaceutical ingredient is an antihistaminic, classified as a second-generation selective H1 receptor, which shows advantages in terms of solubility in contrast with the free base and the trichloride form. Analytical techniques employed were: X ray diffraction, differential scanning calorimetry, thermogravimetric analysis, and infrared spectroscopy. The results were analyzed all together and compared with the information found in literature. Based on the results obtained, it was demonstrated that the analyzed drug samples don´t present any other polymorphic form besides A form, which is the only one reported in literature.